Uncertanties and Risk Analysis on Ports Construction Projects Considering Technological and Market Strategic Factors: A Study in Emerging Countries and Regions - Monteiro Moraes, Rita de Cassia; Negrão MAcedo, Alcebíades; Azevedo Montenegro Duarte, André Augusto; Braga de Moraes, Hito; Pinto de Moraes Neto, Luciano; Pinto Soares, Rodolpho (International Journal for Innovation Education and Research, 2021)
This article appropriates a new methodology for evaluating port projects involving not only economic analysis, but also strategic factors, technological and market, wich provide greater security and assertiveness on the search for the development of a Hub Port model as an option to optimize the logistics of port operations. To achieve the objectives of the proposal, a technical and economic analysis model was developed to demonstrate the feasibility of the project with the inclusion of technological features (deep of ships, modes of transport linking the port to its region of land influence, expansion area) and market components (cargo demands, free trade zone, distance from the main centers of world trade) that decisively interfere in the attractiveness of the project. Linked to this proposal, a risk analysis was carried out, including uncertainties involving economic and strategic aspects, with market and technological variables. To achieve the objectives of the study, the Monte Carlo method operated by the software “@RiskTM” was used, where the analyzes of positive and negative interferences in the project were carried out. To evaluate the proposed methodology, it was applied in two cases studies of the feasibility of a new logistics platform in Brazil and Africa, with the implementation of an offshore cargo concentrator port. One was in the State of Pará, in northern Brazil, and the other in Dakar, Senegal, which can integrate the entire South America and Africa, respectivaly. The results of those analysis show very favorable indicators for the implementation of the proposed projects. Considering that, strategic factors introduced in the study, the greatest influences were: transport modes that link the port to the land influence zone and the draft of the ships. For the offshore port of Pará, strategic factors boosted the viability result by approximately 55% for a 95% probability of success and for Dakar, in Africa, the results were 100%, both for a 14% rate and a life span of 30 years showing that strategic factors are elements very importatants, as they produced almost 100% and 70% elasticity in the results, respectivaly, so they should be considered in feasibility studies of hub ports in addition to tradicioanl economic analysis.